Monetary Policy in Debt System and in Risk-Sharing System - Mirakhor, Abbas (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
This paper critically examines the operations of monetary policy within two fundamentally contrasting financial architectures: the interest-based debt system and the equity-based risk-sharing system. Drawing upon recent global financial developments—particularly the debt distress and monetary tightening episodes of the 2020s—it highlights how conventional monetary policy, centered on interest rate manipulation and fractional reserve banking (FRB), has led to excessive global indebtedness, financial fragility, and widening socioeconomic inequality. The study underscores that in debt-driven systems, monetary expansion often results in wealth concentration among rentier classes and creates systemic moral hazards, whereby financial institutions are shielded from the consequences of their risk-taking behavior through government guarantees and bailouts. In contrast, the risk-sharing model rooted in Islamic economic principles offers a fundamentally different monetary architecture. It proposes a financial system that is closely integrated with the real economy, free from interest-based debt, and governed by participatory contracts such as mudarabah and musharakah. Monetary policy in this system relies on asset-backed, equity-based instruments that align public and private sector incentives, enhance financial inclusion, and promote macroeconomic stability without reliance on pro-cyclical interest rate tools. The paper concludes that transitioning toward a risk-sharing framework presents a viable alternative to the debt-based monetary paradigm, not only in theory but as a necessary step toward achieving long-term sustainability, equitable growth, and resilience against future financial crises.